Alteration of Autonomic Nervous System Is Associated With Severity and Outcomes in Patients With COVID-19 - Pan, Yuchen; Yu, Zhiyao; Yuan, Yuan; Han, Jiapeng; Wang, Zhuo; Chen, Hui; Wang, Songyun; Wang, Zhen; Hu, Huihui; Zhou, Liping; Lai, Yanqiu; Zhou, Zhen; et al. (Frontiers in Physiology, 2021)
Background: Previous studies suggest that coronavirus disease 2019 (COVID-19) is a systemic infection involving multiple systems, and may cause autonomic dysfunction. Objective: To assess autonomic function and relate the findings to the severity and outcomes in COVID-19 patients. Methods: We included consecutive patients with COVID-19 admitted to the 21th COVID-19 Department of the east campus of Renmin Hospital of Wuhan University (a COVID-19-designated hospital) from 6 Feb to 7 Mar 2020. Clinical data were collected. Time-domain and frequency-domain analyses of heart rate variability (HRV), N-terminal pro-B-type natriuretic peptide (NT-proBNP), D-dimer, and the absolute numbers of lymphocytes and lymphocyte subsets were analysed at two time points: nucleic acid test positive and negative. Results: All patients were divided into a mild group and a severe group. The latter was further divided into 2 categories according to the trend of HRV indices. Severe patients had a significantly lower SDNN (P＜0.001) and SDANN (P＜0.001) and a higher LF/HF (P=0.016). Linear correlations were shown among SDNN, SDANN, LF/HF and NT-proBNP, D-dimer, lymphocytes, and lymphocyte subsets (P<0.05). Immune function, D-dimer, and NT-proBNP showed a consistent trend with HRV in severe patients, either towards deterioration or towards improvement (P<0.05). Kaplan-Meier analysis showed that severe patients without improved HRV parameters needed a longer time to clear the virus and recover (P<0.05). Conclusion: HRV was associated with the severity of COVID-19. The changing trend of HRV was related to the prognosis, indicating that HRV measurements can be used as a non-invasive predictor for clinical outcome.